2021
DOI: 10.1080/00498254.2017.1404659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paeoniflorin on the activities and mRNA expression of rat CYP1A2, CYP2C11 and CYP3A1 enzymes in vivo

Abstract: 1. Paeoniflorin is the major constituent in extracts of the peony root, the purpose of the present study was to assess the effects of paeoniflorin on the activities and mRNA expression of the rat hepatic drug-metabolizing enzymes cytochrome P450 (CYP1A2), CYP2C11 and CYP3A1 in vivo. 2. Sprague-Dawley (SD) male rats were treated with paeoniflorin at the dosage of 25, 50 and 100 mg/kg or 0.9% sodium chloride solution by intragastric administration for 7 days, then were given probe drugs phenacetin (CYP1A2), tolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…UHPLC was performed on UltiMate 3000 HPLC (Thermo Fisher Scientific Inc., Chelmsford, MA, U.S.A) as previously reported [16]. Florfenicol and chloramphenicol were simultaneously determined with a Diamonsil C18 column The LOQ and LOD of florfenicol were validated at 0.05 and 0.02 μg/ml, respectively.…”
Section: Uhplc Methods For Detection Of Florfenicol In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…UHPLC was performed on UltiMate 3000 HPLC (Thermo Fisher Scientific Inc., Chelmsford, MA, U.S.A) as previously reported [16]. Florfenicol and chloramphenicol were simultaneously determined with a Diamonsil C18 column The LOQ and LOD of florfenicol were validated at 0.05 and 0.02 μg/ml, respectively.…”
Section: Uhplc Methods For Detection Of Florfenicol In Plasmamentioning
confidence: 99%
“…Total RNA from each sample was isolated by use of TRIzol reagent (Invitrogen Corporation and Applied Biosystems, Inc., Calsbad, CA, USA) according to the manufacturer's protocol. Concentration, purity and integrity of the total RNA samples were measured according to our previous work [16]. RNA samples (800 ng) were reverse transcribed to cDNA with RevertAid Premium Reverse Transcriptase (Thermo Fisher Scientific Inc.) according to the manufacturer's protocol, using C100 PCR (Bio-Rad Laboratories, Inc., Hercules, CA, U.S.A; 2015).…”
Section: Total Rna Isolation and Synthesis Of Cdnamentioning
confidence: 99%
“…UHPLC analyses were performed using an UltiMate 3000 HPLC (Thermo Fisher Scientific Inc., Chelmsford, MA, USA) as previously described [13]. A Diamonsil C18 column (4.6 mm × 250 mm, 5 μm; Thermo Fisher Scientific Inc.) was used to simultaneously detect florfenicol and chloramphenicol at a constant temperature of 40 °C.…”
Section: Uhplc For Detection Of Florfenicol In Plasmamentioning
confidence: 99%
“…GGT with five major ingredients also possesses chance of drug interactions when co-administering with other drugs. A number of in vitro studies investigated the influence of GGT and GGT components on cytochrome (CYP) 450 and predicted its drug interactions [7][8][9][10][11][12][13][14][15][16][17][18][19]. For example, GGT reportedly inhibits CYP2C19, CYP2D6, and CYP2E1 [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GGT reportedly inhibits CYP2C19, CYP2D6, and CYP2E1 [16]. Glycyrrhetic acid completely inhibits CYP3A4 [12], and paeoniflorin inhibits the activity of CYP1A2 in vivo [17]. Wu et al [8] reported that ephedrine induces CYP1A2 activity.…”
Section: Introductionmentioning
confidence: 99%